Relational and Intrapersonal Factors Driving Women’s Engagement in High-Risk Relationships - Batthyany, Karina (Psychology of Woman Journal, 2025)
Objective: This study aimed to explore the relational, intrapersonal, and sociocultural factors that contribute to women’s engagement in and persistence within high-risk intimate relationships.Methods and Materials: A qualitative research design was employed using semi-structured, in-depth interviews with 23 women residing in Mexico who had experienced at least one high-risk romantic relationship characterized by emotional harm, dependency, or coercive dynamics. Participants were recruited through purposive sampling, and data collection continued until theoretical saturation was reached. Interviews were transcribed verbatim and analyzed using thematic analysis supported by NVivo 14 software. Rigor was maintained through member checking, reflexive journaling, and peer debriefing.Findings: Three overarching themes emerged: (1) Emotional Vulnerability and Psychological Needs, including subthemes such as fear of loneliness, low self-worth, emotional dependency, and a need for validation; (2) Interpersonal Dynamics and Power Imbalance, highlighting manipulative control tactics, sexual coercion, and unequal decision-making power; and (3) Sociocultural and Structural Influences, encompassing traditional gender role expectations, economic dependence, stigma, and limited access to mental health support. Participants described enduring harmful relationships due to internalized relational schemas, structural constraints, and cultural narratives that framed endurance as moral strength. Emotional idealization of the partner and hope for redemption were also key drivers for continued engagement in high-risk dynamics.Conclusion: Understanding these multilayered factors is critical for designing culturally responsive, trauma-informed interventions that promote safety, autonomy, and healing. Interventions must address not only individual emotional needs but also systemic barriers to support and empowerment.